Study of the Arguments of the Al-Qur'an and Hadith Permissibility of Cash Waqf in Indonesia - Melis, Melis; Muslim, Aziz; Sahiron, Sahiron; Endraswati, Hikmah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Explicitly, cash waqf does not have specific arguments about its permissibility in the Qur'an or the hadith of the Prophet Muhammad SAW. In Indonesia, the permissibility of cash waqf is determined based on the fatwa of the Indonesian Ulema Council (MUI) dated May 11, 2002. This study aims to review the arguments of the Koran and hadith which form the basis of the MUI fatwa. In examining the meaning of the verses and hadiths, the method of thematic interpretation of terms and fiqh al-hadith is carried out. This study found that, 1) the verse used as the basis for the fatwa is QS. Ali Imran [3]: 92 and (QS. al-Baqarah [2]: 261-262, 2) the traditions used as the basis for the fatwa are those narrated by Ibn Umar and recorded by al-Bukhari, Muslim, al-Tirmidhi, and al-Nasa'I, 3) the arguments of the Qur'an and hadith that are used, although they do not explicitly state about cash waqf, the meaning obtained can explain that cash waqf is a form of waqf that is very possible to implement